A model for simulating spreading processes based on social interactions in complex networks: case studies on online social networks and epidemics - Salem, Feres Azevedo (2023)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Automação e Sistemas, Florianópolis, 2023.